2021
DOI: 10.3390/polym13162729
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Biopolymers for Drugs and Probiotics Delivery

Abstract: Research regarding the use of biopolymers has been of great interest to scientists, the medical community, and the industry especially in recent years. Initially used for food applications, the special properties extended their use to the pharmaceutical and medical industries. The practical applications of natural drug encapsulation materials have emerged as a result of the benefits of the use of biopolymers as edible coatings and films in the food industry. This review highlights the use of polysaccharides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(53 citation statements)
references
References 217 publications
0
40
0
Order By: Relevance
“…The fast-growing notion that encapsulates can be composed of active biomaterials should be driven by matching the material's properties with expected responses through the GIT. Particularly, polymers exhibit versatile molecular moieties that have been widely exploited to fabricate chemical and physical delivery platforms with properties that can be finely tuned by adjusting interchain interactions [51]. Chemical polymeric scaffolds are formed by covalent bonds between adjacent chains, while the physical ones are maintained together by charged polyvalent surfactants or ion interactions [24].…”
Section: Polymeric Platforms and Delivery Systems Of Probioticsmentioning
confidence: 99%
“…The fast-growing notion that encapsulates can be composed of active biomaterials should be driven by matching the material's properties with expected responses through the GIT. Particularly, polymers exhibit versatile molecular moieties that have been widely exploited to fabricate chemical and physical delivery platforms with properties that can be finely tuned by adjusting interchain interactions [51]. Chemical polymeric scaffolds are formed by covalent bonds between adjacent chains, while the physical ones are maintained together by charged polyvalent surfactants or ion interactions [24].…”
Section: Polymeric Platforms and Delivery Systems Of Probioticsmentioning
confidence: 99%
“…Binary TPS/PCL blends aim for technical applications, namely in the field of packaging [ 30 , 31 , 32 ]. As for biomedical applications, the TPS/PCL particles in solution have been considered as possible microcapsules for drug delivery [ 33 , 34 ], but bulk solid TPS/PCL blends have been mentioned in just two studies: Bou-Francis et al [ 24 ] investigated TPS/PCL together with other biodegradable polymer blends as potential fracture fixation devices (which is suspicious due to the very low modulus of PCL/TPS blends) and Mano et al [ 25 ] studied the thermal properties of TPS, which was blended with various synthetic biodegradable polymers including PCL, and concluded that all starch-based blends might be suitable for some medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, synthetic biopolymers have a low cost and high thermal and mechanical properties that distinguishes them from their natural counterparts. [27] The biopolymeric microencapsulated probiotics are generally divided into two major categories being single-and multi-layer microparticles. Single layer microparticles are generally composed of a semipermeable, spherical, thin, and strong membranous wall that retains the probiotics within the structure.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, synthetic biopolymers have a low cost and high thermal and mechanical properties that distinguishes them from their natural counterparts. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%